A new method for designing bis-uracil derivatives as highly efficient and transparent PVC thermal stabilizer with excellent migration resistance. (April 2021) - Shi, Yanqin; Lu, Songyan; Ma, Biao; Chen, Si; Ma, Meng; He, Huiwen; Wang, Xu
Highlights: The bis-uracil derivative, USU-C, with 11 carbon atoms in its long aliphatic chain was synthesized by an optimized method. Thermal stability, transparent performance and migration resistance of USU-C in PVC were better than other reported bis-uracil derivates. The reason was attributed to the better compatibility of USU-C with PVC. A new structural design method of highly transparent and effective bis-uracil derivative thermal stabilizer was proposed according to HSP theory. The quantitative mathematical function between the HSP of bis-uracil derivates and the carbon atom number in the long aliphatic chain was also derived. Abstract: A bis-uracil derivative with a long aliphatic chain of 11 carbon atoms, USU-C, was synthesized by an optimized method. The migration rate test indicated that USU-C had better migration resistance compared to OSU. This advantage enabled the PVC samples containing USU-C to maintain good transparency and low haze for a long time. It had also been proven USU-C has better thermal stability and whiteness retention than OSU by the thermal stability tests. Based on summarizing this work and our previous studies, a new design method was proposed to enhance the transparency and thermal stability effect of thermal stabilizers on PVC based on Hansen solubility parameters (HSP) theory. Impressively, the quantitative mathematical function between the HSP and the carbon atom number in the long aliphatic chain of bis-uracil derivatives was also derived, which could be used to guide the structure design of new bis-uracil derivatives with long term migration resistance, preeminent transparency, and high thermal stability for PVC in the follow-up study, even other organic thermal stabilizers.